2019
DOI: 10.1002/rcm.8527
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polymeric phenolic acids and flavonoids in Clerodendranthi Spicati Herba using ultrahigh‐performance liquid chromatography coupled to quadrupole time‐of‐flight tandem mass spectrometry with target and nontarget data mining strategy

Abstract: Rationale Clerodendranthi Spicati Herba (CSH) is often used to treat urinary stones, urinary tract infections and nephritis in China. Much literature has reported that polymeric phenolic acids and flavonoids are the major bioactive components in CSH. Therefore, it is very meaningful to identify the polymeric phenolic acids and flavonoids in CSH. Methods Ultrahigh‐performance liquid chromatography coupled to quadrupole time‐of‐flight tandem mass spectrometry (UHPLC/QTOF‐MS/MS) analysis with target and nontarget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Peak 3 (195.0514, C 6 H 12 O 7 ) was identified as gluconic acid according to reference [ 28 ]. Peaks 5, 10, 18, and 49 were individually identified as malic acid (133.0148, C 4 H 6 O 5 ), citric acid (191.0200, C 6 H 8 O 7 ), p -coumaric acid (163.0404, C 9 H 8 O 3 ), and azelaic acid (187.0984, C 9 H 16 O 4 ) due to the diagnostic MS/MS fragment ions at 115.002 [M − H − H 2 O] − , 111.0083 [M − H − CO 2 − 2H 2 O] − , 119.0487 [M − H − CO 2 ] − , and 125.0970 [M − H − C 2 H 2 O 2 ] − , respectively [ 29 , 30 ]. Peaks 19, 20, and 24 (C 15 H 18 O 8 ) showed the similar [M − H] − at 325.0938 and similar fragmentation pattern, suggesting they were isomers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peak 3 (195.0514, C 6 H 12 O 7 ) was identified as gluconic acid according to reference [ 28 ]. Peaks 5, 10, 18, and 49 were individually identified as malic acid (133.0148, C 4 H 6 O 5 ), citric acid (191.0200, C 6 H 8 O 7 ), p -coumaric acid (163.0404, C 9 H 8 O 3 ), and azelaic acid (187.0984, C 9 H 16 O 4 ) due to the diagnostic MS/MS fragment ions at 115.002 [M − H − H 2 O] − , 111.0083 [M − H − CO 2 − 2H 2 O] − , 119.0487 [M − H − CO 2 ] − , and 125.0970 [M − H − C 2 H 2 O 2 ] − , respectively [ 29 , 30 ]. Peaks 19, 20, and 24 (C 15 H 18 O 8 ) showed the similar [M − H] − at 325.0938 and similar fragmentation pattern, suggesting they were isomers.…”
Section: Resultsmentioning
confidence: 99%
“…Peak 51 (287.0565, C 15 H 12 O 6 ) had two more hydrogen atoms compared with kaempferol; fragment ions at 259.0611 [M − H − CO] − , 151.0028 [ 1,3 A] − , 125.0239 [ 1,4 A] − allowed the assignment of dihydrokaempferol. Analogously, apigenin (peak 58) and its glycosides (peaks 21, 37, 43), luteolin (peak 54) and luteolin-7- O -hexoside (peak 34), naringenin (peak 59) and its glycosides (peaks 38, 45), myricetin-3- O -hexoside (peak 30), laricitrin-3- O -hexoside (peak 35), syringetin-3- O -hexoside (peak 40), chrysoeriol-7- O -hexoside (peak 44) were proposed by matching the MS and MS/MS data with those recorded in the literature and databases [ 29 , 35 , 41 , 42 ]. The detected fragmentation pattern of peak 58 is shown in Figure 5 e.…”
Section: Resultsmentioning
confidence: 99%
“…Guo et al have identified 21 phenolic acids, 11 MFs, and six diterpenoids in CSH [14]. In our previous study, 85 polymeric phenolic acids and 33 flavonoids were rapidly identified in CSH by UHPLC-QTOF-MS/MS with diagnostic product ions (DPIs) and neutral loss (NL) filtering strategy [15]. In summary, the chemical compositions of CSH include phenolic acids, flavonoids, MFs, diterpenoids, and triterpenoids.…”
mentioning
confidence: 85%
“…The dried CSH (1.2 kg) was cut into pieces and exhaustively extracted twice under reflux with 10 L 80% ethanol (1 h each time). The solution was evaporated in vacuum to afford a residue (129 g) as the ethanol extract [15]. Then, 100 g of ethanol extract was distributed in 200 mL of waterethanol (4: 1, v/v) and loaded on a macroporous resin chromatography column, then eluted with 45 and 95% ethanol to afford two fractions, and after evaporation of the solvent in reduced pressure, the 45% EEF (phenolic acids and flavonoids fraction, 64 g) and 95% EEF (MFs and diterpenoids fraction, 2.9 g) were obtained.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation